Antibiotic use to the production performance of ISA brown layer (Asian Journal of Medical and Biological Research, 2017)
The present study was designed with a view to study the effects of enrofloxacin antibiotic on ISA brown layer performance. A total of 1,80,000 laying hens (ISA brown) received and supplied enrofloxacin antibiotic in the dose of 0 mg, 10mg and 20 mg/kg BW with normal diet. Each layer was fed 120 g feed/day from 42 to 48 weeks of age. Antibiotic made significant differences in egg production (p